2019
DOI: 10.1111/1467-9604.12237
|View full text |Cite
|
Sign up to set email alerts
|

Time, expertise and status: barriers faced by mainstream primary school SENCos in the pursuit of providing effective provision for children with SEND

Abstract: The inclusion ‘ideal’ is one which has been both celebrated and maligned. It paved the way for equality; but also, out of its diversity sprang many misconceptions and concerns for children with Special Educational Needs and Disabilities (SEND). It is within this maelstrom of difficulty that the Special Educational Needs Co‐ordinator (SENCo) role is placed, so that those undertaking the position of SENCo face numerous barriers in the pursuit of providing effectively for children with SEND. Semi‐structured inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 17 publications
2
25
0
Order By: Relevance
“…Such variance echoes the suggestion of Hallett and Hallett (2017) regarding the disparate enactment of the role. 70% of all SENCOs felt that they do not have enough time to fulfil their role, with nearly three‐quarters (74%) stating that they frequently feel frustrated by the lack of time to undertake the role, supporting the findings of Smith and Broomhead (2019) who suggest that the phrase ‘sufficient time’ within the SEND Code of Practice (DfE and DoH, 2015 p. 109) needs to be more specific. The recommendation is that there should be locally or nationally agreed time allocations.…”
Section: Findings and Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…Such variance echoes the suggestion of Hallett and Hallett (2017) regarding the disparate enactment of the role. 70% of all SENCOs felt that they do not have enough time to fulfil their role, with nearly three‐quarters (74%) stating that they frequently feel frustrated by the lack of time to undertake the role, supporting the findings of Smith and Broomhead (2019) who suggest that the phrase ‘sufficient time’ within the SEND Code of Practice (DfE and DoH, 2015 p. 109) needs to be more specific. The recommendation is that there should be locally or nationally agreed time allocations.…”
Section: Findings and Discussionsupporting
confidence: 52%
“…Whilst Smith and Broomhead (2019) have suggested that there should be locally or nationally agreed policy regarding SLT membership for SENCOs, a pragmatic approach would be to accept that the seniority of the role is mixed and to ensure that both approaches are supported. When the SENCO is not part of SLT, Done, Murphy and Watt (2016) would argue that the SENCO needs to understand the process and landscape of senior management, which further highlights the importance of focusing on leadership within the NA SENCO.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 3 more Smart Citations